2013
DOI: 10.1093/bioinformatics/btt303
|View full text |Cite
|
Sign up to set email alerts
|

HitPick: a web server for hit identification and target prediction of chemical screenings

Abstract: Motivation: High-throughput phenotypic assays reveal information about the molecules that modulate biological processes, such as a disease phenotype and a signaling pathway. In these assays, the identification of hits along with their molecular targets is critical to understand the chemical activities modulating the biological system. Here, we present HitPick, a web server for identification of hits in highthroughput chemical screenings and prediction of their molecular targets. HitPick applies the B-score met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 16 publications
0
82
0
Order By: Relevance
“…To gain deeper insights into the molecular basis of these assay combinations, we extracted molecular information of the chemical hits shared by these pairs by annotating predicted human drug targets of the compounds. For that, we applied the HitPick target prediction method (Liu et al , 2013) to predict the molecular targets of hits with high confidence (precision > 50%). Interestingly, we found the same predicted drug targets related to several assay pairs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain deeper insights into the molecular basis of these assay combinations, we extracted molecular information of the chemical hits shared by these pairs by annotating predicted human drug targets of the compounds. For that, we applied the HitPick target prediction method (Liu et al , 2013) to predict the molecular targets of hits with high confidence (precision > 50%). Interestingly, we found the same predicted drug targets related to several assay pairs.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant for the hits of phenotypic assays, for which the underlying molecular targets responsible for their activity is unknown. To determine the protein targets of the chemical hits of these assays, in silico target prediction methods (Keiser et al , 2007; Liu et al , 2013; Wang et al , 2012) are arising as an efficient approach to obtain insights into the compound mode of action. For instance, Young et al have shown recently that the predicted molecular targets of hits are able to explain complex readouts of high-content screening assays (Young et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually assumed that the use of multiple models can increase the prediction accuracy as compared to the use of a single model and help to manage high-dimensional and complex data sets. Similarly to our approach, several other studies have proven that merging a naïve Bayes classifier with a similarity-based approach such as k-nearest neighbors can result in highly predictive models for various applications including the prediction of molecular targets (Ferdousy et al, 2013;Liu et al, 2013). Future investigations could focus on the evaluation of other classification methods (logistic regression, random forests, etc.)…”
Section: Combination Of Features and Algorithmsmentioning
confidence: 90%
“…For example, prediction models have been developed based on the structural similarity of drugs to infer common targets [11,12]. A different approach, not relying on the structural similarity of drugs, predicts drug-target interactions based on the semantic similarity using drug side effects as data source [13].…”
Section: Introductionmentioning
confidence: 99%